Production method of polylactic acid knitted fabric
By introducing flexible branching of alkyl salicylic acid in polylactic acid fibers, the problem of poor toughness of polylactic acid fibers is solved, the elongation and toughness of the fibers are improved, and the production cost is reduced, which is broadened in the textile field. Application prospects.
Patent Information
- Application Number
- CN202411270964.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
AI Technical Summary
The poor toughness of polylactic fibers has limited its application in the textile field. The existing toughening modification methods have problems with poor compatibility and high additive volume requirements.
Alkyl salicylic acid is used as a toughening agent, and flexible branching is introduced through grafting with polylactic acid molecules or self-polymerized ester exchange reaction, reducing crosslinking density and crystallinity, and improving the elongation and toughness of the fibers.
It significantly improves the elongation and toughness of polylactic fibers, reduces production costs, and enhances the mechanical and heat resistance of the fibers.
Smart Images

Figure BDA0005038681590000101 
Figure FDA0005038681570000011
Abstract
Description
Technical Field
[0001] The present application relates to the field of textile technology, and more specifically, to a method for producing a polylactic acid knitted fabric. Background Art
[0002] Polylactic acid (PLA) fiber is one of the "green fibers" with the greatest development prospects. It is environmentally friendly, non-toxic, antibacterial, flame retardant, anti-allergic, biodegradable, and has renewable raw materials. Polylactic acid fiber has excellent physical properties and a wide range of uses. It has high dry and wet strength and initial modulus, good dimensional stability, and the fabric combines the comfort of cotton, the drape of viscose, the strength of polyester, and the feel of silk. It has excellent wearing performance and is widely used in clothing, fabrics, underwear, home textiles, sanitary materials, health care products and other fields.
[0003] Polylactic acid resin can be obtained by ring-opening polymerization of lactide or by direct polymerization of lactic acid. Lactic acid can be obtained by fermentation of starch, which has a wide range of sources. Starch can be used as its raw material from renewable natural plants such as sweet potatoes, corn and other grains. In addition, waste from polylactic acid products can be decomposed into carbon dioxide and water at a controlled rate in nature, which has a very good environmental protection effect. Therefore, as an ideal green fiber, polylactic acid has a broad prospect for sustainable development. The development and application of this fiber is one of the ways to solve white pollution, and it undoubtedly has good social benefits and development prospects.
[0004] As a bio-based green polymer, PLA is expected to partially replace petroleum-based polymers in the future to meet the needs of sustainable development. However, due to its high glass transition temperature (55-65°C), brittleness, low impact strength, poor flexibility and elasticity, and easy bending and deformation, the practical value of PLA is greatly limited. Therefore, PLA materials need to be toughened.
[0005] In order to improve the toughness of PLA, the prior art has adopted many methods, such as stereocompounding, copolymerization modification, blending modification, etc. Among them, blending toughening modification is the lowest cost and simple and effective. The more common blending toughening modification methods include blending with small molecule plasticizers, blending with resin elastomers, blending with rubber particles, etc. The polymers currently used for toughening and modifying polylactic acid fibers include ethylene-vinyl acetate copolymers, polyurethane elastomers, methyl methacrylate-silicon-styrene copolymers, polycaprolactone, starch, etc., but the compatibility between such polymers and polylactic acid is poor, the interaction force is weak, and a high addition amount is required to achieve a good toughening effect, making polylactic acid fibers unsuitable for melt spinning, and their application in the textile field is limited. Summary of the invention
[0006] Compared with PET and PHB, which are also polyesters, PLA does not have -CH2- that can move freely on its main chain. In addition, due to the steric effect of the methyl group and the main chain ester group, the molecular chain is less likely to relax after stretching to offset the influence of stress. As a result, internal stress will accumulate until the molecular chain structure is destroyed, resulting in low elongation at break and poor toughness of PLA.
[0007] In order to solve the above technical problems, the inventors found that after salicylic acid is grafted with alkyl groups, it can be used as a toughening agent for polylactic acid matrix. Alkyl salicylic acid can be grafted on the end of polylactic acid molecules, or it can be self-polymerized in the presence of acid anhydride and then undergo ester exchange reaction with polylactic acid molecules to obtain block copolymers. By introducing flexible side chains into polylactic acid molecules in the above manner, the crosslinking density or crystallinity of the system is reduced, and the long side branch segments have higher mobility, which slows down the stress concentration effect and can absorb energy when subjected to external force, thereby improving the elongation at break of polylactic acid fibers and further improving the toughness of polylactic acid fibers.
[0008] In order to achieve the above technical objectives, the present application provides a method for producing a polylactic acid knitted fabric.
[0009] This application includes the following technical solutions:
[0010] In a first aspect, a polylactic acid toughened fiber is provided, comprising the following components in parts by weight: 70-90 parts of polylactic acid, 3-10 parts of a toughening agent, 0.5-3.5 parts of an acid anhydride, and 0.1-1 parts of an antioxidant;
[0011] The toughening agent is alkyl salicylic acid, and the structural formula is shown in Formula I: Wherein R1 and R2 are alkanes with carbon number ≥ 4.
[0012] Preferably, in the structural formula of the toughening agent, R1 and R2 are straight-chain alkanes having 4 to 8 carbon atoms, and R1 is the same as R2.
[0013] Furthermore, the toughening agent used in this application can be purchased directly or made by yourself. It can be prepared by using salicylic acid and alpha olefin dimer. Alpha olefin dimer is a light component volatile byproduct produced in the petrochemical production process. This application uses it as a raw material to prepare a toughening agent, fully implements the concept of green development, improves its application value, and significantly reduces the raw material price of polylactic acid toughened fiber and reduces production costs.
[0014] Furthermore, the acid anhydride is selected from at least one of acetic anhydride, propionic anhydride, butyric anhydride and isobutyric anhydride.
[0015] Further, the molar ratio of the toughening agent to the acid anhydride is 1:(0.5-1). Preferably, the molar ratio of the toughening agent to the acid anhydride is 1:1.
[0016] Furthermore, the antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076, antioxidant 168, antioxidant 2112, didodecyl alcohol ester, and hydroxybenzotriazole. Preferably, the antioxidant used in the present application is antioxidant 1010.
[0017] Furthermore, the polylactic acid raw material used in the present application is dried before processing to keep its water content below 50 ppm, and the specific drying method adopts high temperature drying. Preferably, the high temperature drying temperature is 60-90°C and the drying time is 4-10 hours.
[0018] In a second aspect, a method for preparing a polylactic acid toughened fiber is provided, comprising the following steps:
[0019] S1, mixing polylactic acid, a toughening agent, an acid anhydride and an antioxidant to obtain a mixture;
[0020] S2, putting the mixed material into an extruder, melting and extruding, cooling and pelletizing, and obtaining a polylactic acid toughened masterbatch;
[0021] S3, melt spinning the polylactic acid toughened masterbatch, and obtaining the polylactic acid toughened fiber after heat drawing and heat setting.
[0022] Furthermore, in step S2, the melt extrusion temperature is 170-220°C, and the screw speed is 250-400rpm.
[0023] Furthermore, in step S3, the melt spinning temperature is 200-240°C, the spinning speed is 2000-3200 m / min, the hot drawing temperature is 80-110°C, the extension ratio of the hot drawing is 1.3-1.8, and the heat setting temperature is 100-120°C.
[0024] In a third aspect, a polylactic acid toughened fiber containing a hydrophilic nanofiller is provided.
[0025] Furthermore, the hydrophilic nanofiller is cellulose nanocrystals. Preferably, the amount of the cellulose nanocrystals is 1-3% based on the total weight of the polylactic acid.
[0026] Furthermore, the polylactic acid toughened fiber containing hydrophilic nanofiller comprises the following components in parts by weight: 70-90 parts of polylactic acid, 3-10 parts of toughening agent, 0.5-3.5 parts of acid anhydride, 0.1-1 parts of antioxidant, and 0.7-2.7 parts of cellulose nanocrystals.
[0027] Cellulose nanocrystals are a type of nanofiller derived from cellulose. Similar to polylactic acid, they also have good biocompatibility and degradability. In addition, the raw materials are widely available and recyclable. When used in polylactic acid, they can significantly improve the mechanical and heat resistance properties of polylactic acid. However, there are a large number of hydrophilic hydroxyl groups on the surface of cellulose nanocrystals, which have poor compatibility with hydrophobic polylactic acid and are easy to agglomerate in the polylactic acid matrix and difficult to disperse. In addition to being directly applied to polylactic acid to improve its toughness, the toughening agent provided in this application can also be used as a surface grafting modifier for hydrophilic fillers such as cellulose nanocrystals, thereby broadening the scope of application of the toughening agent in the field of polylactic acid.
[0028] In a fourth aspect, the present application provides a method for preparing a polylactic acid toughened fiber containing a hydrophilic nanofiller, comprising the following steps:
[0029] S1, adding part of the toughening agent to ethanol and stirring evenly to obtain an alkyl salicylic acid ethanol solution, adding cellulose nanocrystals to the alkyl salicylic acid ethanol solution, stirring and adsorbing for 4-8 hours, and removing the ethanol solvent to obtain grafted cellulose nanocrystals;
[0030] S2, mixing polylactic acid, remaining toughening agent, acid anhydride, antioxidant, and grafted cellulose nanocrystals to obtain a mixture;
[0031] S3, putting the mixed material into an extruder, melting and extruding, cooling and pelletizing, and obtaining a polylactic acid toughened masterbatch;
[0032] S4, melt spinning the polylactic acid toughened masterbatch, and obtaining polylactic acid toughened fibers containing cellulose nanocrystals after heat drawing and heat setting.
[0033] Furthermore, in step S1, the weight ratio of the cellulose nanocrystal to the toughening agent is 1:(0.2-0.5). When the ratio of the cellulose nanocrystal to the toughening agent is 1:0.2, the toughening agent can be completely consumed, but the toughening agent of the present application, in addition to being a surface grafting modifier of the cellulose nanocrystal, also directly acts as a raw material of the polylactic acid fiber to play a toughening role, so the toughening agent can be used excessively during the grafting modification process to increase the surface grafting rate of the cellulose nanocrystal.
[0034] Furthermore, in step S1, the ethanol solvent can be removed by rotary evaporation, condensation recovery, nitrogen purging, vacuum drying, etc. Preferably, the present application adopts rotary evaporation to remove the ethanol solvent, and the evaporation temperature is 55-65°C.
[0035] Furthermore, in step S3, the melt extrusion temperature is 170-220° C., and the screw speed is 250-400 rpm.
[0036] Furthermore, in step S4, the melt spinning temperature is 200-240°C, the spinning speed is 2000-3200 m / min, the hot drawing temperature is 80-110°C, the extension ratio of the hot drawing is 1.3-1.8, and the heat setting temperature is 100-120°C.
[0037] In a fifth aspect, a polylactic acid toughened fiber fabric is provided, wherein the fabric is prepared from the polylactic acid toughened fiber / polylactic acid toughened fiber containing hydrophilic nanofiller provided above through spinning, pretreatment, dyeing, weaving, finishing, shaping and other steps.
[0038] In summary, this application has the following beneficial effects:
[0039] The present application uses alkyl salicylic acid as a toughening agent, which reacts with polylactic acid in a melt reaction, and can significantly improve the elongation at break of the polylactic acid fiber, thereby improving the toughness of the polylactic acid fiber.
[0040] The toughening agent provided in the present application can be directly applied to the polylactic acid matrix to improve the toughness of the polylactic acid fiber, and can also be used as a surface grafting modifier to improve the compatibility and dispersibility of the hydrophilic nanofiller in the polylactic acid matrix, thereby further improving the mechanical and heat resistance of the polylactic acid fiber.
[0041] The fabric prepared by using toughened polylactic acid fiber as textile fiber in this application not only has certain degradability, formability and high toughness, but also has easy-to-obtain raw material sources, relatively low cost, and broad market application prospects. DETAILED DESCRIPTION
[0042] The present application is further described in detail below with reference to embodiments and comparative examples.
[0043] The polylactic acid is American NatureWorks 6202d, which is dried before processing: dried at 65°C for 5 hours, and the water content is controlled below 50ppm.
[0044] Preparation Example
[0045] Preparation Example 1
[0046] Preparation of toughening agent: 13.81 g of salicylic acid, 25 mL of n-butyl ether, 16.83 g of 1-hexene dimer and 3.21 g of methanesulfonic acid were added to a 250 mL single-mouth round-bottom flask. After the addition was completed, the mixture was stirred with a magnetic stirrer, the reaction temperature was controlled at 100°C, the reaction time was 6 h, and then the mixture was filtered and distilled under reduced pressure to obtain 20.59 g of the final product with a conversion rate of 67.2%.
[0047] 1H NMR (400MHz, CDCl3): δ = 10.26 (s, 1H), 7.61 (d, J = 2.5Hz, 1H), 7.48 (dd, J = 8.6, 2.5Hz, 1H), 6.95 (d, J = 8.8H) z,1H), 1.72-1.59(m,2H), 1.50(dddt,J=12.1,9.1,4.9,2.2Hz,2H), 1.36-1.05(m,12H), 1.02-0.78(m,9H)
[0048] LC-MS(ESI+):307.3[M+H] +
[0049] Preparation Example 2
[0050] Preparation of toughening agent: 13.81 g of salicylic acid, 25 mL of n-butyl ether, 224.43 g of 1-octene dimer and 3.21 g of methanesulfonic acid were added to a 250 mL single-mouth round-bottom flask. After the addition was completed, the mixture was stirred with a magnetic stirrer, the reaction temperature was controlled at 100°C, the reaction time was 6 h, and then the mixture was filtered and distilled under reduced pressure to obtain 145.09 g of the final product with a conversion rate of 60.9%.
[0051] 1 H NMR (400MHz, CDCl3): δ = 10.20 (s, 1H), 7.80 (d, J = 2.5Hz, 1H), 7.50 (dd, J = 8.6, 2.5Hz, 1H), 6.98 (d, J =8.8Hz,1H), 1.72-1.60(m,2H), 1.51(dt,J=15.8,8.4Hz,2H), 1.34-1.05(m,20H), 1.02-0.79(m,9H)
[0052] LC-MS(ESI+):363.4[M+H] +
[0053] Preparation Example 3
[0054] Preparation of toughening agent: 15.5 g of salicylic acid, 25 mL of n-butyl ether, 280.53 g of 1-decene dimer and 3.2 g of methanesulfonic acid were added to a 250 mL single-mouth round-bottom flask. After the addition was completed, the mixture was stirred with a magnetic stirrer, the reaction temperature was controlled at 100°C, the reaction time was 6 h, and then the mixture was filtered and distilled under reduced pressure to obtain 163.11 g of the final product with a conversion rate of 55.1%.
[0055] 1H NMR (400MHz, CDCl3): δ = 10.31 (s, 1H), 7.91 (d, J = 2.5Hz, 1H), 7.55 (dd, J = 8.9, 2.5Hz, 1H), 6.98 (d, J = 8.8H) z,1H), 1.75-1.60(m,2H), 1.55(dddt,J=15.4,9.8,5.1,2.2Hz,2H), 1.39-1.09(m,36H), 1.02-0.79(m,9H)
[0056] LC-MS(ESI+):419.4[M+H] +
[0057] Preparation Example 4
[0058] The toughening agent is 5-hexadecyl salicylic acid, purchased from Guangdong Wengjiang Chemical, CAS No.: 28294-58-8.
[0059] Example
[0060] Example 1
[0061] Preparation of polylactic acid fiber:
[0062] S1, weighing and mixing the raw material components as shown in Table 1 to obtain a mixture;
[0063] S2, putting the mixed material into a twin-screw extruder, the screw speed of the extruder is 400 rpm, the temperature of each section of the extruder is set to 140°C, 160°C, 170°C, 180°C, 170°C, and after extrusion, cooling and pelletizing to obtain polylactic acid toughened masterbatch;
[0064] S3, melt spinning the polylactic acid toughened masterbatch, controlling the melt spinning temperature to 200° C. and the spinning speed to 2500 m / min, heat drawing at 80° C. and 1.5 times the stretching ratio, and then heat setting at 100° C. to obtain the polylactic acid toughened fiber.
[0065] in,
[0066] Polylactic acid uses American NatureWorks 6202d, which is dried before processing: dried at 65℃ for 5h, and the water content is controlled below 50ppm;
[0067] The acid anhydride is acetic anhydride;
[0068] The antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and the specific model is antioxidant 1010;
[0069] The toughening agent was prepared according to Preparation Example 1, and the molar ratio of the toughening agent to the acid anhydride was 1:1.
[0070] Example 2
[0071] Preparation of polylactic acid fiber: The process is the same as in Example 1, and the raw material formula is shown in Table 1.
[0072] in,
[0073] Polylactic acid uses American NatureWorks 6202d, which is dried before processing: dried at 65℃ for 5h, and the water content is controlled below 50ppm;
[0074] The acid anhydride is acetic anhydride;
[0075] The antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and the specific model is antioxidant 1010;
[0076] The toughening agent was prepared according to Preparation Example 2, and the molar ratio of the toughening agent to the acid anhydride was 1:1.
[0077] Example 3
[0078] Preparation of polylactic acid fiber: The process is the same as in Example 1, and the raw material formula is shown in Table 1.
[0079] in,
[0080] Polylactic acid uses American NatureWorks 6202d, which is dried before processing: dried at 65℃ for 5h, and the water content is controlled below 50ppm;
[0081] The acid anhydride is acetic anhydride;
[0082] The antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and the specific model is antioxidant 1010;
[0083] The toughening agent was prepared according to Preparation Example 3, and the molar ratio of the toughening agent to the acid anhydride was 1:1.
[0084] Example 4
[0085] Preparation of polylactic acid fiber: The process is the same as in Example 1, and the raw material formula is shown in Table 1.
[0086] in,
[0087] Polylactic acid uses American NatureWorks 6202d, which is dried before processing: dried at 65℃ for 5h, and the water content is controlled below 50ppm;
[0088] The acid anhydride is acetic anhydride;
[0089] The antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and the specific model is antioxidant 1010;
[0090] The toughening agent was prepared according to Preparation Example 4, and the molar ratio of the toughening agent to the acid anhydride was 1:1.
[0091] Example 5
[0092] Preparation of polylactic acid fiber: The process is the same as in Example 1, and the raw material formula is shown in Table 1.
[0093] in,
[0094] Polylactic acid uses American NatureWorks 6202d, which is dried before processing: dried at 65℃ for 5h, and the water content is controlled below 50ppm;
[0095] The acid anhydride is acetic anhydride;
[0096] The antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and the specific model is antioxidant 1010;
[0097] The toughening agent was prepared according to Preparation Example 1, and the molar ratio of the toughening agent to the acid anhydride was 1:0.5.
[0098] Example 6
[0099] Preparation of polylactic acid fiber: The process is the same as in Example 1, and the raw material formula is shown in Table 1.
[0100] in,
[0101] Polylactic acid uses American NatureWorks 6202d, which is dried before processing: dried at 65℃ for 5h, and the water content is controlled below 50ppm;
[0102] The acid anhydride is acetic anhydride;
[0103] The antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and the specific model is antioxidant 1010;
[0104] The toughening agent was prepared according to Preparation Example 1, and the molar ratio of the toughening agent to the acid anhydride was 1:0.8.
[0105] Example 7
[0106] Preparation of polylactic acid toughened fiber:
[0107] S1, the raw material formula is shown in Table 1, 1 / 3 weight of toughening agent is added to 5 times weight of ethanol and stirred evenly to obtain alkyl salicylic acid ethanol solution, cellulose nanocrystals are added to the alkyl salicylic acid ethanol solution, after stirring and adsorbing for 6 hours, the ethanol solvent is removed by rotary evaporation at 60°C to obtain grafted cellulose nanocrystals;
[0108] S2, as shown in Table 1, weigh polylactic acid, remaining toughening agent, acid anhydride, antioxidant, and grafted cellulose nanocrystals of step S1, and mix them to obtain a mixture;
[0109] S3, putting the mixed material into a twin-screw extruder, the screw speed of the extruder is 400 rpm, the temperature of each section of the extruder is set to 140° C., 160° C., 170° C., 180° C., and 170° C., and cooling and pelletizing after extrusion to obtain polylactic acid toughened masterbatch;
[0110] S4, melt spinning the polylactic acid toughened masterbatch, controlling the melt spinning temperature to 200° C. and the spinning speed to 2500 m / min, heat drawing at 80° C. and 1.5 times the stretching ratio, and then heat setting at 100° C. to obtain the polylactic acid toughened fiber.
[0111] in,
[0112] Polylactic acid uses American NatureWorks 6202d, which is dried before processing: dried at 65℃ for 5h, and the water content is controlled below 50ppm;
[0113] The acid anhydride is acetic anhydride;
[0114] The antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and the specific model is antioxidant 1010;
[0115] The toughening agent is prepared according to Preparation Example 1, and the molar ratio of the toughening agent to the acid anhydride is 1:1;
[0116] Cellulose nanocrystals were purchased from MacLean with specifications of: L: ~200 nm, OD: ~10 nm.
[0117] Table 1
[0118] Components / 100g Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Polylactic acid 70 70 70 70 80 90 70 Toughening agent 3 3 3 3 5 10 3 Acid Anhydride 1 0.8 0.7 0.8 0.5 2.7 1 Antioxidants 0.1 0.1 0.1 0.1 0.5 1 0.1 Cellulose Nanocrystals 0 0 0 0 0 0 0.7
[0119] Comparative Example
[0120] Comparative Example 1
[0121] Polylactic acid fiber: The preparation process is the same as that of Example 1, except that the toughening agent and acid anhydride are not used to toughen the polylactic acid.
[0122] Comparative Example 2
[0123] Polylactic acid fiber: The preparation process is the same as that of Example 1. The difference from Example 1 is that when the toughening agent is used to toughen the polylactic acid, no acid anhydride is added.
[0124] Comparative Example 3
[0125] Polylactic acid fiber: The formula is the same as that of Example 7. The difference from Example 7 is that the cellulose nanocrystals are not treated with a toughening agent but are directly mixed with polylactic acid for melt granulation.
[0126] Performance testing
[0127] The performance of the polylactic acid fibers (diameter: 13.6-14.5 μm) prepared in Examples 1-7 and Comparative Examples 1-3 was tested using an electronic single yarn strength tester in accordance with GB / T14337-2008 “Test method for tensile properties of chemical staple fibers”. The test results are recorded in Table 2.
[0128] Table 2
[0129] Test Group Young's modulus / MPa Tensile strength / MPa Elongation at break / % Example 1 2104 78.6 271 Example 2 2940 75.3 250 Example 3 2070 68.1 186 Example 4 1800 72.9 200 Example 5 2011 75.5 240 Example 6 1945 72.8 211 Example 7 3560 81.2 305 Comparative Example 1 1350 60.5 9 Comparative Example 2 1487 63.1 25 Comparative Example 3 1554 65.8 13
[0130] Test results of Comparative Example 1: The Young's modulus, tensile strength and elongation at break of the unmodified PLA are 1350 MPa, 60.5 MPa and 9.5 MPa, respectively, which shows that the tensile resistance and toughness of PLA are poor.
[0131] Test results of Example 1: Compared with Comparative Example 1, Example 1 uses alkyl salicylic acid, acid anhydride and polylactic acid for melt granulation, and the tensile strength of the polylactic acid fiber reaches 78.6MPa (increased by 30%), and the elongation at break is 271% (increased by 29 times), showing both strengthening and toughening effects.
[0132] Test results of Example 7: Compared with Comparative Example 3, Example 7 added cellulose nanocrystals treated with alkyl salicylic acid. It can be seen that compared with Comparative Example 3 which was not treated and directly added, the mechanical properties of the polylactic acid fiber were significantly improved, indicating that alkyl salicylic acid has a positive promoting effect on improving the compatibility between cellulose nanocrystals and polylactic acid materials.
[0133] Test results of Comparative Example 2: Compared with Example 1, in Comparative Example 2, no acid anhydride was added when the toughening agent was blended with polylactic acid. Although the tensile strength and toughness of the obtained PLA fiber were improved to a certain extent compared with the pure PLA fiber, the degree of improvement was limited. This may be because in the absence of acid anhydride, alkyl salicylic acid is difficult to self-polymerize, unable to undergo ester exchange reaction with polylactic acid, and is not easy to embed side chains in the main chain of the polylactic acid molecule. Alkyl salicylic acid is more easily grafted on both ends of the polylactic acid molecular chain, resulting in limited improvement in mechanical properties.
[0134] Application Examples
[0135] Application Example 1
[0136] Polylactic acid fabric: The polylactic acid fiber of Example 1 is used as raw material and is prepared through spinning, pretreatment, dyeing, weaving, finishing and shaping.
[0137] Application Example 2
[0138] Polylactic acid fabric: The polylactic acid fiber of Example 7 is used as raw material and is prepared through spinning, pretreatment, dyeing, weaving, finishing and shaping.
[0139] Application Example 3
[0140] Polylactic acid fabric: The polylactic acid fiber of comparative example 1 is used as raw material, and is prepared through spinning, pretreatment, dyeing, weaving, finishing and shaping.
[0141] Application Example 4
[0142] Polylactic acid fabric: The polylactic acid fiber of comparative example 3 is used as raw material, and is prepared through spinning, pretreatment, dyeing, weaving, finishing and shaping.
[0143] The dyeing process of application examples 1-4 is:
[0144] Dyeing formula: Disperse Yellow E-RGFL 2% (owf), pH=4-5, bath ratio 1:30.
[0145] Dyeing process: dyeing at 20℃→70℃(2℃ / min)→X℃(1℃ / min), keep warm for 35min→soap washing at 50℃(3℃ / min).
[0146] Reduction cleaning formula: hydrosulfite 2g / L, soda ash 1g / L, bath ratio 1:50, temperature 60-65℃, time 15min.
[0147] The CM-3600D computer color measurement and matching system of Italy's ORINTEX company and the M228 soap fastness tester of SILAY-ATLARS were used to test the apparent color depth (K / S value) and color fastness of the polylactic acid fabrics of Application Examples 1-4 at different dyeing temperatures X=120°C, 130°C, and 135°C, respectively. The test results are recorded in Table 3.
[0148] Table 3
[0149]
[0150] When dyeing with disperse dyes, its K / S value and dyeing fastness are closely related to the dyeing temperature. The higher the dyeing temperature, the more favorable it is to the dyeing depth and dyeing fastness of the fabric. From the test results of Application Example 3, it can be seen that when dyeing with disperse yellow E-RGFL, the K / S value of pure PLA fabric at dyeing temperatures of 110℃ and 120℃ is close and reaches a higher value. When the dyeing temperature is 110℃, the soap fastness after dyeing reaches 4-5. PLA fiber has poor heat resistance. When the dyeing temperature exceeds 120℃, PLA fiber softens and loses strength, and PLA fabric melts and agglomerates. Therefore, the maximum dyeing temperature of pure PLA should not exceed 120℃.
[0151] Compared with Application Example 3, the K / S value and soap washing fastness of the polylactic acid fabric in Application Example 1 after dyeing are significantly improved, but the improvement in heat resistance is limited. This may be due to the introduction of flexible alkyl salicylic acid side chains into the polylactic acid molecules, which reduces the crystallinity of the system and makes it easier for the dye molecules to diffuse into the fiber, thereby improving the dyeing depth and color fastness.
[0152] Compared with Application Example 3, Application Example 2 uses cellulose nanocrystals treated with alkyl salicylic acid and polylactic acid for co-extrusion, and the heat resistance of the resulting fabric is significantly improved. The K / S value after dyeing at a dyeing temperature of 130°C is 36.17, and the soap washing fastness is 4-5. The K / S value after dyeing at a dyeing temperature of 135°C is 37.55, and the soap washing fastness is 4. It can be seen that the heat resistance of the polylactic acid fabric is significantly improved. Considering the fastness of the polylactic acid fabric after dyeing, the dyeing temperature is most suitable at 130°C.
[0153] Compared with Application Example 3, in the polylactic acid fiber raw material of Application Example 4, the cellulose nanocrystals are directly melt-granulated with polylactic acid without surface treatment with alkyl salicylic acid. It can be seen that the K / S value and color fastness of the fabric are not significantly improved after dyeing, that is, the heat resistance is not significantly improved. This may be due to the good compatibility between the cellulose nanocrystals treated with alkyl salicylic acid and the polylactic acid material, which can better improve the heat resistance of the polylactic acid fiber.
[0154] The above is only the preferred implementation of the present application. The protection scope of the present application is not limited to the above embodiments. All technical solutions under the concept of the present application belong to the protection scope of the present application. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present application should also be regarded as the protection scope of the present application.
Claims
1. A method for producing a polylactic acid knitted fabric, characterized in that: The method uses polylactic acid toughened fiber as raw material, and includes the following preparation steps: spinning, pretreatment, dyeing, weaving, finishing, and shaping; The dyeing formula: Disperse Yellow E-RGFL 2% (owf), pH = 4-5, bath ratio 1:30; Dyeing process: 20℃ dyeing → 70℃ (2℃ / min) → 110-135℃ (1℃ / min), keep warm for 35min → 50℃ soap washing (3℃ / min); Reduction cleaning formula: hydrosulfite 2g / L, soda ash 1g / L, bath ratio 1:50, temperature 60-65℃, time 15min; The polylactic acid toughened fiber comprises the following components in parts by weight: 70-90 parts of polylactic acid, 3-10 parts of toughening agent, 0.5-3.5 parts of acid anhydride, and 0.1-1 parts of antioxidant; The toughening agent is alkyl salicylic acid, and the structural formula is shown in Formula I: Wherein R1 and R2 are alkanes with carbon number ≥ 4.
2. The method for producing polylactic acid knitted fabric according to claim 1, characterized in that: In the toughening agent structural formula, R1 and R2 are straight-chain alkanes with 4 to 8 carbon atoms, and R1 is the same as R2.
3. The method for producing polylactic acid knitted fabric according to claim 1, characterized in that: The acid anhydride is selected from at least one of acetic anhydride, propionic anhydride, butyric anhydride and isobutyric anhydride, and the molar ratio of the toughening agent to the acid anhydride is 1:(0.5-1).
4. The method for producing polylactic acid knitted fabric according to claim 3, characterized in that: The molar ratio of the toughening agent to the acid anhydride is 1:
1.
5. The method for producing polylactic acid knitted fabric according to claim 1, characterized in that: The antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076, antioxidant 168, antioxidant 2112, didodecanol ester, and hydroxybenzotriazole.
6. The method for producing polylactic acid knitted fabric according to claim 1, characterized in that: The polylactic acid toughened fiber also includes 0.7-2.7 parts by weight of cellulose nanocrystals.
7. The method for producing a polylactic acid knitted fabric according to any one of claims 1 to 5, characterized in that: The polylactic acid toughened fiber comprises the following preparation steps: S1, mixing polylactic acid, a toughening agent, an acid anhydride and an antioxidant to obtain a mixture; S2, putting the mixed material into an extruder, melting and extruding, cooling and pelletizing, and obtaining a polylactic acid toughened masterbatch; S3, melt spinning the polylactic acid toughened masterbatch, and obtaining the polylactic acid toughened fiber after heat drawing and heat setting.
8. The method for producing polylactic acid knitted fabric according to claim 6, characterized in that: The polylactic acid toughened fiber comprises the following preparation steps: S1, adding part of the toughening agent to ethanol and stirring evenly to obtain an alkyl salicylic acid ethanol solution, adding cellulose nanocrystals to the alkyl salicylic acid ethanol solution, stirring and adsorbing for 4-8 hours, and removing the ethanol solvent to obtain grafted cellulose nanocrystals; S2, mixing polylactic acid, remaining toughening agent, acid anhydride, antioxidant, and grafted cellulose nanocrystals to obtain a mixture; S3, putting the mixed material into an extruder, melting and extruding, cooling and pelletizing, and obtaining a polylactic acid toughened masterbatch; S4, melt spinning the polylactic acid toughened masterbatch, and obtaining polylactic acid toughened fibers containing cellulose nanocrystals after heat drawing and heat setting.
9. The method for producing polylactic acid knitted fabric according to claim 8, characterized in that: The weight ratio of the cellulose nanocrystals to the toughening agent is 1:(0.2-0.5).
10. A polylactic acid toughened fiber fabric, characterized in that: The fabric is prepared by the production method of polylactic acid knitted fabric according to any one of claims 1 to 6.
